Factors influencing readmission among Thais with myocardial infarction - Rapin Polsook; Yupin Aungsuroch (Belitung Raya Foundation, Indonesia, 2021)
Background: Readmission among patients with myocardial infarction is costly, and it has become a marker of quality of care. Therefore, factors related to readmission warrant examination. Objective: This study aimed at examining factors influencing readmission in Thai with myocardial infarction. Methods: This was a cross-sectional study with 200 participants randomly selected from five regional hospitals in Thailand. All research tools used indicated acceptable validity and reliability. Linear Structural Relationship version 8.72 was used for the data analysis. Results: The findings showed that the hypothesized model with social support, depression, symptom severity, comorbidity, and quality of life could explain 4% (R2 = 0.04) of the variance in readmission (c2 = 1.39, df = 2, p < 0.50, c2/df = 0.69, GIF = 1.00, RMSEA = 0.00, SRMR = 0.01, and AGFI = 0.98). Symptom severity was the most influential factor that had a positive and direct effect on the readmission rate (0.06, p < 0.05). Conclusions: These findings serve as an input to decrease readmission in patients with myocardial infarction by reducing the symptom severity and comorbidity and promoting a better quality of life.